Cascade of Care in the Legal System: Best Practices and Goals for Agencies Providing Care to Patients Concurrently Navigating Substance Use Disorders and Criminal Legal Involvement - Clark, Kendra J. (Journal of drug issues, 2025)
Fewer than 1% of United States’ largest corrections facilities allow access to MOUD. The cascade of care is an organizing framework that quantifies treatment processes within and across systems of care ranging from screening to treatment discharge. This study highlights best practices for the implementation of MOUD across the cascade of care, addressing unique characteristics of legal settings and individuals within them. After reviewing best-practices for MOUD implementation in legal settings and examining jail and community provider’s use of and goals toward improving these practices, this study concludes that despite interest from agencies to improve care considerable variation remains in treatment availability between agencies and within agencies at different stages of incarceration. Seamless systems of care require multiagency collaboration, staff and provider competency, and patient awareness of MOUD. These strategies will decrease punishment-oriented ideologies surrounding MOUD application in justice settings and improve access to resources that remove barriers to care.